31P NMR spectroscopy of rat organs, in situ, using chronically implanted radiofrequency coils. - Koretsky, A P (1983)
A technique for making 31P NMR spectroscopic measurements in rat kidney, heart, and liver in vivo is presented. Two-turn solenoid coils were surgically implanted around the organ sufficiently in advance of NMR experiments to allow recovery of the animal. These chronically implanted coils allowed acquisition of high-resolution spectra at 40.5 and 97.3 MHz. No resolution improvement occurred at the higher field. Spectra were stable for up to 24 hr, during which time a variety of experiments could be performed. By accumulating spectra at 10-min intervals, the effects of intraperitoneal fructose injections were monitored; in kidney and liver, a rapid increase in sugar phosphates at the expense of Pi and ATP resulted. Fructose had no effect on heart metabolite levels. Spectra from the heart in vivo were obtained at systole and diastole by gating the spectrometer to the aortic pressure wave; no differences in phosphate metabolites were detected. Finally, saturation transfer techniques were used to monitor the rate of ATP synthesis in the kidney. The unidirectional rate constant for the conversion of Pi to ATP was 0.12 +/- 0.03 sec-1.